Os impactos dos herbicidas em abelhas nativas: uma revisão sistemática sobre as nossas bases de dados - Lopes, Lucas Teodoro (Universidade Federal de São Carlos, 2023)
Knowledge of the toxicological effects resulting from pesticides on our native bees is of unique importance for understanding their extent and consequently carrying out appropriate management for their conservation. This work carried out a systematic review covering all the articles we have published in Portuguese and English that evaluated the effects of herbicides on native Brazilian bees, a class that has great prominence in its commercialization and application in fields. Thus, after determining the eligibility criteria and carrying out research on the "Google Scholar" and "SciELO Brasil", a total of 24 selected articles were identified. From this selection, it was possible to observe some standardizations and challenges present in the current database that we use as a basis for discussions on the subject. Among the main points discussed, the focus on the use of glyphosate as the dominant molecule in Evaluations of this class drew attention due to the death values, so that 19 (79.17%) of the 24 articles chosen used this molecule, either as the only herbicide or together with another, and of these nineteen, 17 (70.83%) used it as the only herbicide evaluated. Other molecules were used in only 20.83% of the articles chosen, which represents approximately 10% of all articles collected. Even with a market share equivalent to 59.24% among the ten most sold herbicides, its proportion in academic research increased by 19.56% in its representativeness. When we sought to base this disproportion on the environmental risks presented by each molecule, we found that, according to official IBAMA reports, glyphosate would not be more harmful than other herbicides, not justifying its more intensive study, removing this possible bias from the discussions. Regarding the sublethal effects observed, in total 11 different categories were raised, indicating a lack of standardization in the data obtained in comparison to the herbicides evaluated, generating little data to be validated by different studies, which creates gaps for statements regarding the effects generated by these active ingredients.
The impacts of herbicides on native bees: a systematic review of our databases
Keywords: Comercialização; Comparativo; Efeitos letais; Efeitos suletais; Pesticidas; Commercialization; Comparative; Lethal effects; Sublethal effects; Pesticides; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE